Adipose and Muscle Tissue Gene Expression of Two Genes (NCAPG and LCORL) Located in a Chromosomal Region Associated with Cattle Feed Intake and Gain - Lindholm-Perry, Amanda K. (Public Library of Science, 2013)
A region on bovine chromosome 6 has been implicated in cattle birth weight, growth, and length. Non-SMC conodensin I complex subunit G (NCAPG) and ligand dependent nuclear receptor corepressor-like protein (LCORL) are positional candidate genes within this region. Previously identified genetic markers in both genes were associated with average daily gain (ADG) and average daily feed intake (ADFI) in a crossbred population of beef steers. These markers were also associated with hot carcass weight, ribeye area and adjusted fat thickness suggesting that they may have a role in lean muscle growth and/or fat deposition. The purpose of this study was to determine whether the transcript abundance of either of these genes in cattle adipose and muscle tissue was associated with variation in feed intake and average daily gain phenotypes. Transcript abundance for NCAPG and LCORL in adipose and muscle tissue was measured in heifers (adipose only), cows and steers using real-time polymerase chain reaction. In the adipose tissue from cows and heifers, a negative correlation between LCORL transcript abundance and ADFI were detected (P = 0.05). In the muscle tissue from cows, transcript abundance of NCAPG was associated with ADG (r = 0.26; P = 0.009). A positive correlation between LCORL transcript abundance from muscle tissue of steers and ADFI was detected (P = 0.04). LCORL protein levels in the muscle of steers were investigated and were associated with ADFI (P = 0.01). These data support our earlier genetic associations with ADFI and ADG within this region and represent the potential for biological activity of these genes in the muscle and adipose tissues of beef cattle; however, they also suggest that sex, age and/or nutrition-specific interactions may affect the expression of NCAPG and LCORL in these tissues.